1992
DOI: 10.1007/bf01253110
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution and in vivo binding of the atypical antipsychotic drug remoxipride. A biochemical and autoradiographic analysis in the rat brain

Abstract: The regional brain distribution and binding of the antipsychotic benzamide drug remoxipride was studied in the male rat. After i.v. injections of 3H-remoxipride (1 mumol.kg-1) more than 85% of the radioactivity was identified as authentic remoxipride in brain by using reversed-phase liquid chromatography. Autoradiographic and spectroscopic analysis showed that 3H-remoxipride was distributed relatively even in different brain areas, with exception of the following structures, which showed highest drug concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…There is limited evidence for regional differences in 0 2 receptor occupancies after acute administration of a few compounds, e.g., remoxipride (Kohler et al 1992), but no studies have shown this to be the case after repeated administrations leading to a steady state level of drug in brain. Further, receptor inactivation studies in vivo using EEDQ have suggested that remoxipride (acute treatment) binds to a subpopulation (unspecified) of 0 2 receptors .…”
Section: Effects In Models For Antipsychotic and Eps Activity Limbic mentioning
confidence: 99%
“…There is limited evidence for regional differences in 0 2 receptor occupancies after acute administration of a few compounds, e.g., remoxipride (Kohler et al 1992), but no studies have shown this to be the case after repeated administrations leading to a steady state level of drug in brain. Further, receptor inactivation studies in vivo using EEDQ have suggested that remoxipride (acute treatment) binds to a subpopulation (unspecified) of 0 2 receptors .…”
Section: Effects In Models For Antipsychotic and Eps Activity Limbic mentioning
confidence: 99%
“…In the pre-injection design FLA 797(-) was more effective than remoxipride, FLA908(-) and NCQ436(-) in preventing quinpirole-induced hypothermia. NCQ 436(-), which is the major metabolite in plasma and urine following remoxipride administration to the rat (Widman et al, 1992), was the least effective and also had a shorter action than remoxipride, probably due to rapid metabolic inactivation (Widman etal., 1992). When the antagonists were given after the agonists, remoxipride was as effective as NCQ436(-) (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Remoxipride binds to dopamine (DA) D 2 and sigma recepetors in vitro, while its affinity towards other neurotransmitter receptors is very low (K6hler etal., 1990;Malmberg etal., 1993). Most of the effects of remoxipride relevant for its antipsychotic properties are observed in rodent studies in the same dose-range as the compound inhibits in vivo binding in the brain of the DAD 2 receptor antagonist [3H]spiperone or [3H]raclopride (K6hler et al, 1992;Ogren et al, 1984). This indicates that the pharmacological effects of remoxipride in the rat most likely are mediated by blocking DAD 2 receptors.…”
Section: Introductionmentioning
confidence: 93%
“…Remoxipride, an antipsychotic agent, is transported from the CP vascular bed to the CSF and thereafter to the interstitial fluid of the medial caudate nucleus, hippocampus, thalamus, and cerebellum. One hour after injection of 3 H-remoxipride, there is a gradient of radioactivity from the ventricles to deep regions of the cerebrum including the forebrain (83). This pattern of drug distribution from CP to CSF to brain is similar to that of vitamin C. Autoradiograms reveal that intravenous 14 C ascorbate rapidly penetrates the BCSFB (but not the BBB).…”
Section: Caudatey Yputamenmentioning
confidence: 92%